Factores que influyen en las decisiones de financiamiento y su relación con el crecimiento empresarial de las pymes de la ciudad de Iquitos, año 2019 - Padilla Arévalo, Lito (2021)
The objective of this research was to determine the relationship between financing decisions and business growth of SMEs in the city of Iquitos, year 2019, it was carried out under a descriptive-correlational investigation with a non-experimental design, the sample consisted of 228 entrepreneurs, who were surveyed using the questionnaire instrument; reaching the following results that the financing decisions of SMEs is deficient (22%) according to the perception of the respondents, since they do not manage a cash flow for their financing or enjoy its benefits, likewise, the investments are almost never evaluated. More profitable sources for fundraising, however, are constantly looking to make higher profits. On the other hand, it was determined that business growth is of a regular level (24%) according to the perception of entrepreneurs, since SMEs sometimes promote staff development through programs, decisions are almost never made based on the perception of employees. workers and management, neither the problems are solved equitably, finally, the labor commitment is sometimes high. Finally, it was concluded that there is a significant relationship between financing decisions and business growth of SMEs in the city of Iquitos, in 2019, with a significance of 0.000 and a correlation coefficient (rho) of 0.766, this being positive and considerable.